Ord från norr : svensk skönlitteratur på den franska bokmarknaden efter 1945 - Hedberg, Andreas, 1979- (Stockholm University Press, 2022)
The flow of literature from Sweden to France is unlike anything else. Canonized authors such as August Strindberg and Selma Lagerlöf have been surprisingly successful in translating into French. The same applies to later high-prestige literature by Torgny Lindgren and P O Enquist. French publishers were also among the first to discover the Swedish detective story writers. The rights to Stieg Larsson's Millennium trilogy were bought by a French publisher before the novels began to be published in Swedish. Children's literature, on the other hand, perhaps Sweden's foremost contribution to world literature, had a late breakthrough in the French book market. This also applies to Astrid Lindgren, the incomparably most successful of all authors translated from Swedish. Why did Swedish fiction receive this particular reception in France? This book describes how Swedish literature has been translated into French, with a special focus on the period after 1945. During this period, the number of editions of Swedish fiction in French has increased tenfold. Which translators, publishers and other actors have contributed to this development? How have they reasoned and acted to promote the interests of Swedish literature? What types of literature and authorship have been particularly successful? These questions are answered on the basis of comprehensive statistics based on the latest bibliographic lists. The book also discusses the theoretical conditions for this type of study. The leading researchers in world literature research - Pascale Casanova, David Damrosch and Franco Moretti - are related to a literary sociological study of the book's communities.